MiR-129-5p Protects H9c2 Cardiac Myoblasts From Hypoxia/Reoxygenation Injury by Targeting TRPM7 and Inhibiting NLRP3 Inflammasome Activation. Issue 5 (May 2021) - Liu, Shuke; Liao, Qingchi; Xu, Wei; Zhang, Zhen; Yin, Minming; Cao, Xiaohu
Abstract : Abstract: As a biomarker for heart failure, miR-129-5p is abnormally expressed during myocardial I/R, but its specific functions and mechanisms remain largely unclear. Thus, this study explored the roles and possible mechanisms of miR-129-5p in hypoxia/reoxygenation (H/R)-insulted H9c2 cardiac myoblasts. After H/R insult, miR-129-5p expression levels were decreased, along with reduced cell viability and enhanced lactate dehydrogenase release in H9c2 cells. Overexpression of miR-129-5p through transfection of miR-129-5p mimics effectively improved cell viability and reduced lactate dehydrogenase release in H9c2 cells exposed to H/R, along with decreased apoptosis and caspase-3 activities. Moreover, miR-129-5p mimics inhibited reactive oxygen species production and upsurged superoxide dismutase activity in H9c2 cells exposed to H/R, and suppressed H/R-caused massive release of proinflammatory cytokines TNF-α and IL-1β. TRPM7 was identified as the target of miR-129-5p and was negatively regulated by miR-129-5p. TRPM7 overexpression counteracted the antagonistic effect of miR-129-5p on H/R-induced increase in intracellular calcium levels. TRPM7 overexpression also abolished miR-129-5p-induced elevation on cell viability and reduction on apoptosis as well as attenuated miR-129-5p-induced inhibition on reactive oxygen species and IL-1β production. Besides, H/R-induced NLRP3 inflammasome activation was inhibited by miR-129-5p mimic but reactivated by TRPM7. In conclusion, miR-129-5p alleviates H/R injury of H9c2 cardiomyocytes by targeting TRPM7 and inhibiting NLRP3 inflammasome activation, suggesting that miR-129-5p and TRPM7 may be potential therapeutic targets for myocardial I/R injury. Abstract : Supplemental Digital Content is Available in the Text.